1994
DOI: 10.2331/fishsci.60.455
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Malt Protein Flour in Fingerling Rainbow Trout Diets

Abstract: Two feeding experiments were conducted to evaluate malt protein flour (MPF) as an alternative protein source for the diet of rainbow trout Oncorhynchus mykiss fingerlings. MPF is a new protein rich by-product from brewer's spent grain. Experiment 1 was conducted to clarify the suitable substitution level of MPF for white fish meal (WFM) in the diet. The control diet, containing WFM as the sole protein source, and isonitrogenous (40% crude protein) experimental diets, containing MPF substituted for 20 to 80% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…In the present study, dietary WG content (3–17%) was below the maximum recommended level. On the contrary, it has been reported that malt flour, obtained from the by‐product of beer distillation, was not palatable for trout Oncorhynchus mykiss (Yamamoto, Marcouli, Unuma & Akiyama 1994). Yamamoto, Unuma, Akiyama and Kishi (1996) also noted that high inclusion levels of malt protein flour in the diet decreased the rate of feed consumption in red sea bream Pagrus major .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, dietary WG content (3–17%) was below the maximum recommended level. On the contrary, it has been reported that malt flour, obtained from the by‐product of beer distillation, was not palatable for trout Oncorhynchus mykiss (Yamamoto, Marcouli, Unuma & Akiyama 1994). Yamamoto, Unuma, Akiyama and Kishi (1996) also noted that high inclusion levels of malt protein flour in the diet decreased the rate of feed consumption in red sea bream Pagrus major .…”
Section: Discussionmentioning
confidence: 99%
“…Fingerlings of rainbow trout Oncorhynchus mykiss were obtained at the Shiga Prefectural Samegai Trout Farm (Maibara, Shiga) and those of common carp Cyprinus carpio at the Yahagigawa Fisheries Cooperative Associations (Toyota, Aichi), and transferred to the Inland Station of the National Research Institute of Aquaculture (Tamaki, Mie). The fingerlings were reared in the same manner as described previously 13,14 until use for fecal collection. The rearing conditions for fecal collection are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The ratio of dietary fat from animal and vegetable origins was adjusted to 1:2 by the addition of pollock visceral oil (Riken Vitamin Co. Ltd, Tokyo, Japan) and soybean oil (Wako Pure Chemical Industries Ltd, Osaka, Japan). The ingredients were thoroughly mixed and made into dry pellets according to the method described in Yamamoto et al 21 The pellets were stored at −20°C until being fed to the fish.…”
Section: Methodsmentioning
confidence: 99%